Photon Shielding Features of Quarry Tuff - Malvagi, F.; Vega Carrillo, Héctor René; Hernández Adame, Luis; Guzmán García, Karen Arlete; Ortiz Hernández, Arturo Agustín; Rodríguez Rodríguez, José Antonio; Juárez Alvarado, César Antonio; Malouch, F.; Diop, C. M’. B.; Miss, J.; Trama, J. C. (2017)
Abstract. Cantera is a quarry tuff widely used in the building industry; in this work the shielding features of cantera were determined. The shielding characteristics were calculated using XCOM and MCNP5 codes for 0.03, 0.07, 0.1, 0.3, 0.662, 1, 2, and 3 MeV photons. With XCOM the mass interaction coefficients, and the total mass attenuation coefficients, were calculated. With the MCNP5 code a transmission experiment was modelled using a point-like source located 42 cm apart from a point-like detector. Between the source and the detector, cantera pieces with different thickness, ranging from 0 to 40 cm were included. The collided and uncollided photon fluence, the Kerma in air and the Ambient dose equivalent were estimated. With the uncollided fluence the linear attenuation coefficients were determined and compared with those calculated with XCOM. The linear attenuation coefficient for 0.662 MeV photons was compared with the coefficient measured with a NaI(Tl)-based -ray spectrometer and a 137Cs source.